Hands-On Experiments in the Interactive Physics Laboratory: Students’ Intrinsic Motivation and Understanding - Marie Snětinová; Petr Kácovský; Jana Machalická (Center for Educational Policy Studies Journal)
Experiments in different forms can certainly be suitable tools for increasing student interest in physics. However, educators continuously discuss which forms of experimenting (if any) are the most beneficial for these purposes. At the Faculty of Mathematics and Physics, Charles University, Prague, two different forms of physics experiments are offered to upper secondary students: hands-on experimental work in the Interactive Physics Laboratory, and physics demonstration shows where the students watch experiments conducted by a lecturer. Our research focuses primarily on student feedback about their immediate attitudes towards these two projects. Data collection was undertaken using questionnaire research based on the Intrinsic Motivation Inventory. This research was subsequently supplemented with a qualitative study examining the influence of students’ experimental work in the Interactive Physics Laboratory on their understanding of selected physics concepts. The results of the main research show that the two projects do not exhibit significant differences in terms of student interest and perceived usefulness; nevertheless, students felt the need for significantly more effort and experienced pressure during their work in the Interactive Physics Laboratory. One interesting finding, which goes against our original hypothesis, is that grades in physics are quite a strong predictor of students’ assessment of the projects: better grades indicate more positive assessment of both projects as well as less pressure felt during hands-on activities in the laboratory.